Vulnerable Workers: Profile of Drug Abusers - Lisa, Mona; Tunggal Mutika, Winnie; Rismiawati, Riris; Sulistyorini, Dwi (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Introduction The use of illicit drugs is a global epidemic, with prevalence varying depending on the type of drug and the location of use (Degenhardt and Wall, 2012). Social factors at the individual, family, and community levels are associated with the initiation and use of illicit drugs. The use of illicit drugs that is prevalent among young adult males with sufficient economic status can negatively impact the productivity of future generations (Blumstein, 1995). Objective : Objective The objective is to identify the characteristics of respondents who were illicit drug users in Indonesia in 2017. The characteristics examined include gender, education level, marital status, closeness to family, risk environment, access to drugs, and workplace location. Research Methods/ Implementation Methods : Method This research design uses a cross-sectional study. Data were obtained from a national survey conducted by the National Narcotics Board (BNN) and Center for Health Research, University of Indonesia, in 2017. This survey was conducted on groups of workers in various cities and districts throughout the provinces in Indonesia, with a sample size of 34,397 respondents. Data collection used a structured questionnaire filled out by the respondents themselves. The analysis used is a descriptive Results : Result The results of the study showed the characteristics of drugs. where men were 77.8%, medium education was 60.5%, married were 51.5%, closeness to family was 84.5%, non-risk environment was 64.6%, difficult access to drugs was 78.0%, and urban areas were 57.9%. Conclusion/Lesson Learned : The results of this study indicate that despite family support and limited access to drugs, drug abuse continues to occur, especially in certain population groups. These findings highlight the importance of a more holistic prevention approach, which takes into account social and environmental factors to reduce future drug abuse.